دراسـة تحليلية لـ 48 حالة داء زلاقي عند البالغين - زيزفون, حسان (Latakia University Journal -Medical Sciences Series, 2019)
الداء الزلاقي اعتلال مناعي ذاتي للأمعاء الدقيقة، يصيب الأشخاص المؤهبين وراثياً. وتثار الحديثة المناعية فيه بتناول البقول الحاوية على الغلوتين مما يؤذي الأمعاء الدقيقة ويفقدها مقدرتها على امتصاص المواد الطعامية ويسبب سوء التغذية واختلاطات أخرى متنوعة. عندما يصيب الأطفال، يتظاهر الداء الزلاقي بالأعراض الوصفية لمتلازمة سوء الامتصاص "إسهالات مزمنة - نقص وزن - تطبل بطن". أما عند البالغين فإن الأشكال غير الوصفية التي تتعلق بأعضاء وأجهزة غير الأمعاء هي الأكثر مشاهدة. تهدف هذه الدراسة لتحليل التظاهرات السريرية والموجودات المخبرية المختلفة للمرضى البالغين المصابين بالداء الزلاقي، وقد أجريت الدراسة بين نيسان 2001 وكانون أول 2004 وتضمنت 48 مريضاً (17 رجلاً و31 امرأة). ممن أظهرت لديهم خزعة الأثنى عشري وجود ضمور تام أو تحت تام في الزغابات المعوية، وتراوحت أعمارهم بين 14 - 60 سنة "وسطياً 24 سنة". تبين لنا: يصيب الداء الزلاقي النساء أكثر من الرجال ونسبة النساء/الرجال هي 1.8. شخصت أغلب الحالات في العقد الثالث من العمر. وتكون النساء بسن أصغر من الرجال عند التشخيص 93% من النساء هن دون الثلاثين من العمر مقابل 76% من الذكور. يسيطر الوهن العام وفقر الدم على اللوحة السريرية فهي تصادف لدى حوالي 80%. أما الإسهالات المزمنة فتأتي في الدرجة الثانية وتشاهد لدى نصف المرضى وهي جيدة التحمل ولا تؤدي لنقص الوزن والوذمات إلا في نسبة ضئيلة من المرضى. من الناحية المخبرية: اختبار امتصاص الدي-كسيلوز D-Xylose طبيعي لدى 41% من المرضى. ولم تتجاوز إيجابيته الشديدة 19% من الحالات وكانت إيجابيته أقل لدى 39% من المرضى. المعايرة المصلية لأضداد الغليادين Anti Gliadin Antibodies IgA إيجابية في 82% من الحالات، والمعايرة المصلية لأضداد الأندوميزيوم Endomysium Antibodies IgA إيجابية في 92% من الحالات. أهم الاضطرابات المخبرية الأخرى كانت فقر الدم بعوز الحديد، ونقص كالسيوم الدم. Celiac Disease "CD" is an auto immune disease of small intesine in genetically susceptible individuals. The immune-mediated enteropathy is triggered by the ingestion of gluten containing grains. The auto immune response causes damage to small intestine leading to loss of it's ability to absorb the nutrient of the food, and leading to malnutrition and other complications. When affected children CD manifest typical malabsorption syndrome "chronic diarrhea, weight loss, abdominal distension", but in the adults the extra intestinal forms of CD are much more frequent than classical pediatric forms of the disease. The objective of this study is to analyse the clinical manifestations and laboratory findings of the adult celiac disease cases. From April 2001 to December 2004 we enrolled 48 patients (17 men and 31 women; mean age 24 years; range, 14 - 60 years). All patients presented total or subtotal villous atrophy in duodenal biopsy. We found that CD affects females more than males with sex ratio 1.8. The majority of patients is in the third decade. The diagnosis of CD is earlier in female patients than in the males, 93% of affected women are under thirty against 76% of the men. Fatigue and anemia predominate the tableau clinic, they are present in more than 80%, while only 54% of patients suffer from diarrhea which is tolerated and leads only in few cases to weight loss and edema. D-Xylose test is normal in 41% of our patients, markedly positive in 19% and of suspected value in 39% of them. The serology of Anti Gluten Antibodies (AGA) IgA is positive in 82% of patients and the Endomysium Antibodies (EMA) is positive 92% of cases. The most important other laboratory abnormalities are iron deficiency Anemia and hypocalciemia.